Onodera Punpun’s Changing Forms: A Reflection of Emotional and Psychological Growth in Oyasumi Punpun - Michelle Carolina Wahyudi; Setefanus Suprajitno (Kata Kita: Journal of Language, Literature, and Teaching, 2026)
Oyasumi Punpun by Inio Asano is a slice-of-life manga that explores psychological depth through its protagonist, Onodera Punpun. This study examines the symbolic meanings behind Punpun’s eight changing forms and how they reflect his emotional and psychological states. The visual contrast between Punpun and other realistically drawn characters sparked interest in exploring these forms. Using Erikson’s Psychosocial Development Theory, Punpun’s growth is categorized into school age, adolescence, and young adulthood. Semiotic analysis is also applied to interpret the connotations, denotations, and myths behind each form. The findings show his transformations mirror inner struggles, childhood reflects innocence and dependency, adolescence shows identity confusion through three distinct forms and young adulthood presents emotional turmoil and eventual acceptance. These symbolic shifts reveal how manga effectively portrays mental health and emotional development.